Dom Rodrigo de Sousa Coutinho and the crisis of the old colonial system - Silva, Felipe dos Santos (Revista Crítica Histórica, 2020)
POMBO, Nívia. Dom Rodrigo de Sousa Coutinho: political-administrative thought and action in the Portuguese Overseas Empire (1778-1812). São Paulo: Hucitec, 2015.